UMP Postgraduate Open Day opportunity for prospective students to further study - Siti Nurfarmy, Ibrahim (2021)
PEKAN, 5 June 2021 - The public and prospective students had the opportunity to meet the staff and lecturers of Universiti Malaysia Pahang (UMP) virtually at the Postgraduate Open Day held online on 5 and 6 June recently. It was the best platform for prospective students to obtain information related to postgraduate programmes offered by UMP on a full- or part-time basis and provide an opportunity for all potential candidates to choose UMP as their next higher education institution.